The physical education and environmental education: an analysis on the construction of toys with recycled materials in school space (Research, Society and Development, 2020)
The present research aims to understand how the making of toys with recyclable materials, from a playful and interdisciplinary perspective, contributes to the child's development in the municipality of Encanto-RN. A qualitative approach was used, carrying out an action research in a class of the 3rd year of Elementary School, enrolled at the Antônio Pereira da Silva Municipal School, located at Sítio Carnaubinha, in the municipality of Encanto Rio Grande do Norte. The intervention was carried out weekly through didactic workshops with the students, for five weeks, in the months of July and August 2019. Based on the results and discussions and based on the experiences lived along this trajectory of the workshops, it is worth saying that the construction of the toy, goes beyond the development of new skills, also passing through the knowledge of the student, his conception of the world and the internalization that each one makes of the object. All of this brought an understanding of our role as teachers, our pedagogical practice that needs to be reshaped in everyday life at school, based on the students' reality. Despite the short time, it was considerable and relevant to the development and learning obtained by children, as it is indisputable the recognition of the importance of this pedagogical practice in Physical Education for teaching child learning, where it is evident that this practice is inserted in the school environment, working on environmental awareness and reusing discarded materials for the construction of toys, and thus arousing a greater interest of the child to expand his autonomy and more effective participation in the educational process.